Flexural Response of RC Beams with Variable-Width Prestressed and Non-Prestressed CFRP Plate Strengthening - Al-Khafaji, Yasir Safaa; Al-Zuhairi, Alaa Hussein (Salehan Institute of Higher Education, 2026)
This experimental research was conducted to quantify the combined effect of the external bonded Carbon Fiber Reinforced Polymer (CFRP) plate width and prestressing on the flexural performance of reinforced concrete (RC) beams in terms of strength improvement. Seven beams (one control and six strengthened) were subjected to two-point loading tests. The experimental methodology consisted of the testing of three different widths of the CFRP plates (25, 40, and 60 mm) in non-prestressed and prestressed conditions. Prestressing was accomplished by tensioning the plates to 23% of the CFRP tensile strength using a novel, locally developed mechanical anchorage system, which is one of the key experimental contributions that distinguishes this study from investigations that vary only one parameter. Results showed that although non-prestressed CFRP increased the ultimate load by 22.4%-32.3%, prestressed strengthening had superior gains ranging from 29.8% to 67.6%. Prestressed beams had similar ultimate deflections, which greatly enhanced crack control. Notably, prestressing successfully changed the critical failure mode from partial debonding to beneficial CFRP rupture, validating the efficiency of the anchorage system and CFRP-stress utilization. The results show that increasing plate width improves capacity and that suggests that the combination of width and prestress parameters must be optimized for balanced structural design.